Investigation of the antioxidant properties of extracts of spent coffee grounds - Milić Anita S.; Tepić-Horecki Aleksandra N.; Škaljac Snežana B.; Šumić Zdravko M.; Cvetković Biljana R.; Pavlić Branimir M.; Jokanović Marija R. (Food and Feed Research)
Coffee is one of the most consumed beverages worldwide. During coffee processing, a significant amount of by-products is generated, with coffee grounds being the primary byproduct resulting from both beverage preparation and instant coffee production. The yield of bioactive compounds extracted from coffee grounds depends on the type of coffee and its growing and processing conditions. The antioxidant activity of coffee grounds is mainly attributed to their high phenolic content. The main goal of this study was to investigate the antioxidant activity of dried coffee grounds remaining in the machine after espresso preparation, focusing on determining the total phenolic content, flavonoids and antioxidant activity through FRAP, DPPH and ABTS tests. Four solvents were used for the extraction and isolation of antioxidant components: 70% ethanol, distilled water and mixtures of 70% ethanol: water in different ratios (70% water and 30% ethanol, and 30% water and 70% ethanol). Based on the research results, it was concluded that the solvents of ethanol and its mixtures with water present a better solution for maximizing the contents of phenols and flavonoids, as well as for achieving the highest antioxidant activity in spent coffee grounds extracts. The results of this research also suggest that coffee waste could be used as a significant source of bioactive compounds, provided that appropriate extraction solvents are used. This study highlights the potential of spent coffee grounds as a sustainable source of antioxidants, contributing to the reduction of food waste. By valorizing coffee waste, this research is in line with sustainability goals and offers a valuable approach to recycling food by-products.